Making Social Investment Happen for the Eurozone - Anton C. Hemerijck (Intereconomics, 2016)
Half a decade after the euro crisis, the European Union is in dire need of a growth strategy that is economically viable, politically legitimate and seen as socially fair. The United Kingdom's fateful choice for Brexit has given new urgency to this imperative. While it is deplorable to lose a strong political force behind the internal market, Britain's decision to leave the EU does create a window of opportunity for taking the Union's “social market economy” ambitions, as laid down in Articles 2 and 3 of the Lisbon Treaty, more seriously than before.
Keywords: 330